2006
DOI: 10.1108/02634500610641561
|View full text |Cite
|
Sign up to set email alerts
|

Does culture matter on the web?

Abstract: PurposeInvestigating one aspect of the potential of firms to market their offerings internationally, this research seeks to explore the impact of that familiar topic – culture – on online international marketing. More precisely, whether the technologies of the web (manifest in the graphical user interface (GUI)) are culturally neutral, allowing for transparent communication between different cultures.Design/methodology/approachUtilising the widely cited cultural dimensions of culture – “uncertainty avoidance” … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 5 publications
1
33
0
Order By: Relevance
“…Different reactions of consumers with various cultural backgrounds to information technologies and innovations lead to divergent attitudes towards online shopping (Gong, 2009;Dwyer et al, 2005). Studies conducted by various researchers demonstrate that culture affects the expectations and perceptions of consumers on e-commerce (Moon et al, 2008;Yoon, 2009;Pookulangara and Koesler, 2011) and it differentiates their attitudes to transactions encountered during online shopping such as purchase, payment, delivery etc (Sakarya and Soyer, 2013;Burgmann et al, 2006). Therefore it is obvious that firms have to take various cultures into account when they determine their strategies despite the homogenization of markets due to unprecedented access to all around the world with only "one click" (Capece et al, 2013;Mazaheri et al, 2014).…”
Section: Culture and Consumer Behaviourmentioning
confidence: 99%
“…Different reactions of consumers with various cultural backgrounds to information technologies and innovations lead to divergent attitudes towards online shopping (Gong, 2009;Dwyer et al, 2005). Studies conducted by various researchers demonstrate that culture affects the expectations and perceptions of consumers on e-commerce (Moon et al, 2008;Yoon, 2009;Pookulangara and Koesler, 2011) and it differentiates their attitudes to transactions encountered during online shopping such as purchase, payment, delivery etc (Sakarya and Soyer, 2013;Burgmann et al, 2006). Therefore it is obvious that firms have to take various cultures into account when they determine their strategies despite the homogenization of markets due to unprecedented access to all around the world with only "one click" (Capece et al, 2013;Mazaheri et al, 2014).…”
Section: Culture and Consumer Behaviourmentioning
confidence: 99%
“…Whether they are good predictors for UI preferences has been heavily debated, with some researchers doubting the validity of the dimensions (Khashman and Large 2010;Oshlyansky 2007). Others, however, have demonstrated that certain dimensions can be linked to users' design choices with some success (Burgmann et al 2006;Callahan 2005;Dormann and Chisalita 2002). We build on his work because Hofstede's dimensions are the only national cultural classification that has been used to link tangible country scores to UI preferences.…”
Section: The Intangible Nature Of Culturementioning
confidence: 99%
“…How much preferences differ between countries becomes clear from research comparing websites designed by East Asian companies with those designed by their Western counterparts (Burgmann et al 2006;Callahan 2005;SchmidIsler 2000). Findings in this research area repeatedly emphasize that national culture influences our perception of good design.…”
mentioning
confidence: 99%
“…This result strongly recommends that culture awareness is necessary to improve management of cross-cultural online communication (Burgmann, Kitchen & Williams, 2006). Several studies analyze content of websites according to a cross-cultural perspective (Burnett & Buerkle, 2004), cultural adaptation of websites improving effectiveness of companies' internationalization strategies.…”
Section: A Hofstede's Cultural Dimensions Theorymentioning
confidence: 99%